Studi Kasus Analisis Perilaku Korban Bullying dan Penanganannya di Sekolah Menengah Atas - Ramadhani, S, Nurhidayah; Latif, Suciani; Harum, Akhmad (Indonesian Journal of School Counseling: Theory, Application, and Development, 2024)
The aim of this research is to find out: Description of the behavior of victims of bullying, factors that cause problematic behavior in victims and efforts to deal with behavioral problems of victims of bullying at SMAN 2 Jeneponto. The approach used in this research is a qualitative approach with a clinical case study type of research. Data collection uses interviews and observations. The data sources in this research are the subject (SS), classmates and guidance and counseling teachers. The results of this research show that: (1) Description of the forms of behavior of victims of bullying, namely the behavior of withdrawing from their new environment, difficulty forming/building relationships in friendships, Not confident, Difficult to express the feelings experienced. (2) The factors that cause the behavior of victims of bullying in SS subjects are internal factors: the SS subject's lack of self-control, wrong perceptions and being shy. As for external factors: caused by family and peers. Efforts are made to deal with behavioral problems of victims of bullying using behavioral contract techniques. After the intervention was given, SS subjects were slowly able to reduce behavior that was considered problematic.